1997
DOI: 10.1038/nsb0697-463
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the hepatitis C virus RNA helicase domain

Abstract: Helicases are nucleotide triphosphate (NTP)-dependent enzymes responsible for unwinding duplex DNA and RNA during genomic replication. The 2.1 A resolution structure of the HCV helicase from the positive-stranded RNA hepatitis C virus reveals a molecule with distinct NTPase and RNA binding domains. The structure supports a mechanism of helicase activity involving initial recognition of the requisite 3' single-stranded region on the nucleic acid substrate by a conserved arginine-rich sequence on the RNA binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
423
0
7

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 435 publications
(436 citation statements)
references
References 30 publications
6
423
0
7
Order By: Relevance
“…One of the remarkable features of all three available helicase structures (Subramanya et al, 1996;Korolev et al, 1997;Yao et al, 605…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the remarkable features of all three available helicase structures (Subramanya et al, 1996;Korolev et al, 1997;Yao et al, 605…”
Section: Resultsmentioning
confidence: 99%
“…IA). The second view of a helicase was that of the RNA helicase domain of the NS3 protein of hepatitis C virus (HCV) (Yao et al, 1997) (Fig. 1B).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…RNA helicases are a diverse class of enzymes that use the energy of nucleoside triphosphate (NTP) hydrolysis to unwind duplex RNA+ They are involved in virtually every aspect of RNA metabolism, including transcription, splicing, translation, export, ribosome biogenesis, mitochondrial gene expression, and the regulation of mRNA stability (Schmid & Linder, 1992;Lohman & Bjornson, 1996;de la Cruz et al+, 1999;Linder & Daugeron, 2000)+ On the basis of conserved sequence motifs, and the arrangement of these motifs, both RNA and DNA helicases have been divided into three large superfamilies and two smaller families+ The superfamilies are called SF1, SF2, and SF3 (Gorbalenya et al+, 1989b;Gorbalenya & Koonin, 1993)+ More than a decade ago, nearly all double-stranded and positive-stranded (ϩ) RNA viruses were predicted to encode putative helicases (Gorbalenya & Koonin, 1989)+ Indeed, apart from the RNA-dependent RNA polymerases (RdRp), they are the most conserved subunits of the RNA virus replication machinery (Koonin & Dolja, 1993)+ Also, there is extensive genetic evidence to suggest a key function for helicases in the life-cycle of (ϩ) RNA viruses (for reviews, see Buck, 1996;Kadaré & Haenni, 1997)+ However, despite their importance, the reactions catalyzed by (ϩ) RNA virus-encoded helicases have not been well defined and their precise role in virus replication is poorly understood+ Thus, for example, from the large group of putative RNA virusencoded helicases, only members of SF2 have been associated with duplex-unwinding activity+ In this respect, the hepatitis C virus NS3 (HCV NS3) protein is the best-characterized enzyme+ Structural analyses using X-ray crystallography (Yao et al+, 1997;Cho et al+, 1998;Kim et al+, 1998) have shown that HCV NS3 is structurally related to the Bacillus stearothermophilus PcrA and Escherichia coli Rep SF1 DNA helicases+ All three enzymes share two subdomains, 1A and 2A, that represent an internal repeat of RecA-like subdomains (Subramanya et al+, 1996;Korolev et al+, 1997;Yao et al+, 1997;Velankar et al+, 1999)+ Also, it is increasingly clear that the 1A and 2A subdomains, which represent the "core helicase," may be decorated with additional domains to produce specific enzymatic activities (Bird et al+, 1998;Korolev et al+, 1998)+ The biochemical characterization of HCV NS3, together with other RNA virus-encoded SF2 enzymes, has revealed that these proteins share a 39-to-59 polarity in their unwinding activities (for reviews, see Kadaré & Haenni, 1997; Kwong et al+, 2000)+ The m...…”
Section: Introductionmentioning
confidence: 99%
“…The bound ssDNA is in a configuration more similar to that found in a DNA duplex, with the bases stacked against one another, unlike the extended conformation observed in PcrA. Interestingly, the RecD2 mode of binding is more similar to that seen in SF2 enzymes such as NS3, Rad54, Vasa, and Hel308 [104,[123][124][125] rather than SF1A helicases [126].…”
Section: Structure Of Sf1b Helicases (Recd2 and Dda)mentioning
confidence: 86%